Redefining Multicultural Competence of Students in Indonesian Higher Education: Meta-analysis Approach - Abduh, Amirullah; Haris, Hasnawi; Rosmaladewi, Rosmaladewi; Muslim, Abu (Universitas Negeri Makassar, 2023)
Multicultural competence is an important skill for university students so that they are able to engage locally, nationally and globally. This research aims to redefine multicultural competence using meta-analysis approach. The meta-analysis uses key published prominent papers in the area of multicultural competence in the last five years. The published papers are taken as a representative sample in the area of multicultural competence and that are closely related to the lexical item of multicultural competence. The result of the study indicated that this redefinition of multicultural competence encompasses the notion of multicultural competence both in western and non-western contexts. This study has pedagogical implications where university students who engage globally should possess global pre-requisite which is multicultural competence. Thus, universities can allocate both formal and normal engagement programs to foster students’ multicultural competences.